COMPETITION IN THE BRAZILIAN MOBILE TELEPHONY SEGMENT - Schnaider, Paula; Dias Fouto, Nuno Manoel Martins; Saes, Maria Sylvia Macchione; de Angelo, Claudio Felisoni (Future Studies Research Journal: Trends and Strategies, 2011)
Although there were 152 million mobile phones in Brazil as of January 2009, a research conducted by the International Communications Union in 2008 revealed that amongst the 154 countries surveyed, Brazilian users paid the most for the use of mobile phones. Between 2008 and 2009, Anatel introduced mobile number portability as a measure that would promote greater competition amongst operators. This article sought to evaluate the impacts of this policy on competition in the Brazilian mobile telephony segment, particularly as to fees charged. To this effect, both a static and a dynamic analytical framework were built, based on the Prisoners‟ Dilemma Game-Theoretic Model. Theoretical propositions were compared to empirical data related to the mobile fees charged in São Paulo and indicated that the implementation of the mobile number portability policy did not bring about the reduction of fees charged to consumers. This finding contradicts the price reduction phenomenon that occurred in other countries after implementing the portability policy and suggests the need for further rulings which pose to encourage carriers to charge lower fees.